2011
DOI: 10.1055/s-0031-1281752
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Anti-Angiogenic Therapy in Metastatic Colorectal Cancer (mCRC): Original Data and Review of the Literature

Abstract: We examined circulating endothelial progenitor cells (EPC), serum-VEGF levels and the tumour tissue VEGF expression of patients with mCRC under a bevacizumab containing chemotherapy. The patients with a partial remission after six months of immuno-chemotherapy showed a reduction of CD 34 negative KDR positive cells as early as 3 weeks after start of therapy. Neither serum nor tissue markers were of significant predictive value in our pilot study. Furthermore, we review the current data on biomarkers for anti-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…Jalbăet al (2011) showed VEGF-A expression as a poor prognostic marker for CRC in their study (Jalbă et al, 2011). In other study; there was found no correlation between treatment response and VEGF expression within the tumour tissue (Pohl et al, 2011).…”
Section: Discussionmentioning
confidence: 75%
“…Jalbăet al (2011) showed VEGF-A expression as a poor prognostic marker for CRC in their study (Jalbă et al, 2011). In other study; there was found no correlation between treatment response and VEGF expression within the tumour tissue (Pohl et al, 2011).…”
Section: Discussionmentioning
confidence: 75%
“…A number of potential biomarkers have been evaluated, one after another, in clinical studies, including circulating endothelial progenitor cells (EPCs), circulating endothelial cells (CECs), VEGF serum levels, VEGF tissue expression, serum angiopoietin-2, gene polymorphisms of patients, visceral fat areas, blood pressure, and so on; however, few of them have demonstrated significant predictive value until now [29,30,31,32,33,34]. Moreover, it has been postulated that patients who have elevated pretreatment levels of the plasma soluble form of VEGF receptor (VEGFR)-1 or increased levels of stromal cell-derived factor-1αα (SDF1α) are not likely to benefit from anti-VEGF therapies, which has yet to be verified in further clinical studies [27].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to chemotherapy (including anti-angiogenic target therapy), a significantly decreased CEPCs concentration was demonstrated in three studies [69,72,76], whereas others reported no significant changes [22,79], and another presented a remarkably higher EPCs level post-treatment [75]. Roodhart et al analyzed the changes in CEPCs in a cohort of patients receiving chemotherapy and found that the increase in EPCs level started a few hours after the initiation of chemotherapy, exceeded to 114 % (95 % CI 78-151 %; NS) after 7 days and continued to increase to 304 % (95 % CI 176-1,431 %; P \ 0.01) on day 21, and was not limited to the regimens applied in the chemotherapy [75].…”
Section: Cepcs As An Indicator Of Treatment Responsementioning
confidence: 99%
“…However, the assessment of these parameters cannot reflect the efficacy immediately and directly, thus necessitating a reliable surrogate biomarker. The potential of CEPCs in the prediction and response monitoring to a therapeutic intervention is determined by distinguishing the impact of various interventions (e.g., surgery, chemotherapy, and radiation) on CEPCs in different cancers, including breast cancer [59,72], head and neck cancer [60], lung cancer [22,54,76], ovarian cancer [61,63], RCC [66,67], colorectal cancer [79], multiple myeloma [69], glioma [56], gastric cancer [74], and mixed types [75] (Table 3). In all studies, the CEPCs levels were quantified by FACS technique, which are not presented in Table 3.…”
Section: Cepcs As An Indicator Of Treatment Responsementioning
confidence: 99%